Establishment of New Highly Insulin-Sensitive Cell Lines and Screening of Compounds to Facilitate Glucose Consumption - Kenji Hayata; Katsuichi Sakano; Shigeyuki Nishinaka (Elsevier, 2008)
To obtain compounds that promote glucose uptake in muscle cells, the novel cell lines A31-IS derived from Balb/c 3T3 A31 and C2C12-IS from mouse myoblast C2C12 were established. In both cell lines, glucose consumption was induced by insulin and suppressed by the addition of Akt-activating kinase inhibitor. The A31-IS cells highly express the insulin receptor β chains, Glut4, and uncoupling protein-3, as compared to the parent Balb /c 3T3 A31 cells, and C2C12-IS cells highly express the insulin receptor β chain as compared to its parent cell line. Using A31-IS cells, we screened our library compounds and obtained three compounds, DF-4394, DF-4451, and DG-5451. These compounds dose-dependently promoted glucose consumption in A31-IS cells and facilitated [3H]-2-deoxyglucose uptake in differentiated C2C12-IS cells. The compounds that we obtained from the library screening will be good candidates for improving insulin resistance in muscle cells. Keywords:: skeletal muscle cell, insulin, glucose uptake